2021
DOI: 10.1128/msystems.01337-20
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Emulsifier P80 Intake Induces Gut Dysbiosis in Offspring and Increases Their Susceptibility to Colitis in Adulthood

Abstract: Early life events can lead to multiple diseases in adulthood. Previous studies suggested that polysorbate 80 (P80) as a widely used emulsifier in pharmaceutical formulations and food industries could impair the intestinal barrier. However, whether maternal P80 (MP80) exposure could affect the long-term health of offspring remains unknown. In this study, we found that maternal P80 intake could retard intestinal development, disrupt the intestinal barrier, and cause low-grade intestinal inflammation in 3-week-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 80 publications
1
25
0
Order By: Relevance
“…The TJ plays an important role in maintaining the integrity of the intestinal barrier. The loss of barrier integrity increases the translocation of bacterial antigens and stimulates the inflammatory response of intestinal mucosa (Jin et al, 2021). In our results, the number of GC, the expression of MUC2 and tight junction protein in the gut tissues of CAC mice were increased by EVO.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The TJ plays an important role in maintaining the integrity of the intestinal barrier. The loss of barrier integrity increases the translocation of bacterial antigens and stimulates the inflammatory response of intestinal mucosa (Jin et al, 2021). In our results, the number of GC, the expression of MUC2 and tight junction protein in the gut tissues of CAC mice were increased by EVO.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, correlation analysis revealed that Bacteroides and Parasutterella were positively correlated with inflammatory factors and negatively correlated with intestinal barrier integrity, while Alloprevotella was the opposite. Microbial dysbiosis and intestinal barrier dysfunction are considered to be two important pathogenic factors that trigger colitis (Jin et al, 2021). Our study showed that EVO inhibited the AOM/DSSinduced colitis through regulating the gut microbiota.…”
Section: Discussionmentioning
confidence: 53%
“…The microbiota can be transmitted from mothers to infants through a variety of ways, including feces, vaginal delivery, skin, and breastfeeding. Therefore, maternal gut microbiota has a significant impact on the microbial composition of offspring [ 7 ]. However, the stability of gut microbiota may fluctuate with aging-related factors such as physiologic, lifestyle, and health status [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Table 1 [ 3 , 4 , 9 , 10 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], the danger in recent public health failures is not simply that time and money was expended in unsuccessfully combatting the NCD epidemic. It is that some of the recommendations actually further erode both the microbiome and human health.…”
Section: The Updated Science–application Gap: Ancient Personal Responsibility Solutions To Stop Ncdsmentioning
confidence: 99%